Brongniartia herbacea (Leguminosae, Papilionoideae) a new species from Michoacán, Mexico - Grether, Rosaura; Rzedowski, Jerzy (Instituto de Ecología, A.C., 2015)
Brongniartia herbacea, a new taxon, endemic to northern Michoacán, is described and illustrated. It is related to the species of the B. podalyrioides Kunth and B. inconstans S. Watson group.